APLICABLE HORIZONTAL WIND TURBIN MODEL FAMILY SCALE - Rahayu, Nitabian Iftita; Jumali, Muhamad Abdul (UNIPA PRESS, 2019)
The aplicabel of horizontal wind turbine. There is two alternative two develop wind turbine design that generator or blade, in order to develop horizontal wind turbine This reesearch select the partdesign to develop generator. The angle design betwen coil and magnetic field must to optimal degree. There are seven angle from 60 degree to 120 degee which angle test. There is range of the optimal degree from 80 degree to 100 degree to develop wihd turbine.